Hydroxy-α-sanshool isolated from Zanthoxylum bungeanum Maxim. has antidiabetic effects on high-fat-fed and streptozotocin-treated mice via increasing glycogen synthesis by regulation of PI3K/Akt/GSK-3β/GS signaling - Zhang, Qing; Li, Ruo-Lan; Wang, Ling-Yu; Zhang, Ting; Qian, Die; Tang, Dan-Dan; He, Cheng-Xun; Wu, Chun-Jie; Ai, Li (Frontiers in Pharmacology, 2022)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disease characterized by hyperglycemia. The fruits of Zanthoxylum bungeanum Maxim. is a common spice and herbal medicine in China, and hydroxy-α-sanshool (HAS) is the most representative amide in Z. bungeanum, and it’s reported HAS has significant hypoglycemic effects. The purpose of this study was to evaluate the ameliorative effect of HAS on T2DM and its potential mechanism. Acute toxicity test revealed the median lethal dose (LD50) of HAS was 73mg/kg. Furthermore, C57BL/6J mice were fed with high-fat diet and intraperitoneal injection of streptozotocin (STZ) to prepare T2DM mice to evaluate hypoglycemic effects of HAS. The results showed HAS significantly reduced the fasting blood glucose, improved the pathological changes of liver and pancreas, and increased liver glycogen content. In addition, glucosamine (GlcN) induced HepG2 cells was used to establish insulin resistance cell model and explore the molecular mechanisms of HAS. The results showed HAS significantly increased glucose uptake and glycogen synthesis of HepG2, and HAS could activate the PI3K/Akt pathway in GlcN -induced HepG2 cells, increase GSK-3β phosphorylation, deactivate phosphorylation of glycogen synthase (GS), and increase glycogen synthesis in liver cells. Furthermore, these effects of HAS could be blocked by PI3K inhibitor LY294002. In summary, our present study suggested HAS could improve hepatic insulin resistance and increase hepatic glycogen synthesis by activating PI3K/Akt/GSK-3β/GS signaling pathway.